A method, product and use of polymer self-assembly for the preparation of high entropy carbide ceramic materials

CN118955141BActive Publication Date: 2026-10-27NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411011369.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-26
Publication Date
2026-10-27
Estimated Expiration
2044-07-26

AI Technical Summary

Benefits of technology

[0023]本发明高熵碳化物陶瓷材料的制备方法与传统的固相粉末高能球磨法相比,无需对原材料进行机械合金化和高能球磨,热解过程无需特殊的烧结设备,不会在球磨过程中发生氧化以及引入杂质元素,无需二次破碎球磨、工艺路线简单安全;与现有碳热还原法相比,利用过渡金属乙酰丙酮盐与苯酚类化合物或苯醇类化合物的配位反应形成络合物,再通过缩合反应获得元素分子级别均匀分散的聚合物溶液,合成的单相高熵碳化物陶瓷材料纯度高、成分和粒径均匀可控,所需的热解温度从2000℃以上降低至1800℃以下;与熔盐法相比,无需对合成粉体进行复杂繁琐的除杂过程。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118955141B_ABST
    Figure CN118955141B_ABST
Patent Text Reader

Abstract

The application discloses a method for preparing high-entropy carbide ceramic materials based on polymer self-assembly, a product and an application, and belongs to the technical field of ceramic materials. The method comprises the following steps: mixing and stirring organic compounds and at least four kinds of transition metal acetylacetone salts in an organic solvent to obtain a mixed solution; the organic compounds are phenol compounds or phenol compounds; resin crosslinking agents and catalysts are added into the mixed solution to generate a condensation reaction, and a high-entropy carbide ceramic precursor solution is obtained; after washing and drying, a high-entropy carbide ceramic precursor powder is obtained; and the high-entropy carbide ceramic precursor powder is pyrolyzed at 1500-1800 DEG C for 1-3 hours, and the high-entropy carbide ceramic material is obtained. The method has the advantages of low synthesis and pyrolysis temperature, simple process, high controllability, high purity of the prepared high-entropy carbide ceramic material, and excellent thermal performance and mechanical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of ceramic materials technology, specifically relating to a method, product, and application for preparing high-entropy carbide ceramic materials based on polymer self-assembly. Background Technology

[0002] Carbide ceramics, as excellent thermal structural materials, possess advantages such as high temperature resistance, oxidation resistance, high strength, good fracture toughness, and thermal shock resistance, and have been widely used in the hot-end protection structures of high-speed aircraft. However, carbide ceramics can only be used in high-temperature oxidizing environments with short operating times, which severely limits their application in ultra-high temperature and long-term oxygen-containing environments.

[0003] High-entropy carbide ceramics are carbide ceramics with a single crystal structure composed of multiple transition metals from Groups IV, V, and VI in equimolar or near-equimolar ratios. Due to the high entropy, lattice distortion, hysteretic diffusion, and component gain effects of high-entropy carbide ceramics, they exhibit higher high-temperature strength, good high-temperature stability, and tunable performance, providing a new approach for the development of high-performance ceramic materials.

[0004] Currently, the main methods for preparing high-entropy carbide ceramics include high-energy ball milling, solution processing, molten salt processing, and carbothermal reduction. For example, Chinese patent document CN109180189A discloses a high-entropy carbide ultra-high temperature ceramic powder and its preparation method. This ceramic powder is prepared by ball milling and mixing at least two metal powders (at least two of Zr, Ti, Hf, V, Nb, Ta, Cr, Mo, or W) with C powder, followed by pressureless discharge plasma sintering. However, the ball milling method consumes a lot of energy, and oxidation and the introduction of impurity elements may occur during the ball milling process. Chinese patent document CN116514553A discloses a composite carbide ceramic powder. This invention relates to materials, their preparation methods, and applications. It utilizes the reaction of metal alkoxides with a carbon source to obtain a liquid-phase carbide precursor (in the combined action of anhydrous ethanol and acetylacetone, the chloride ions of transition metal chlorides are completely replaced, yielding a metal alkoxide). Tetraethyl orthosilicate, after catalytic hydrolysis, reacts with the liquid-phase carbide precursor to obtain a composite carbide ceramic powder. This composite carbide ceramic powder is then subjected to distillation, curing, and high-temperature heat treatment to obtain ceramic powder. The aforementioned solution method, using metal chlorides as raw materials, not only suffers from the problem of easily hydrolyzing metal alkoxy bonds formed with alcohol solvents, severely affecting the stability of the precursor and the molecular-level uniform dispersion of metal elements, but also has the problem of Cl present in the precursor. -The heat treatment process can also cause damage to the human body and equipment. In addition, although the carbothermal reduction method is a widely used synthesis method, it is difficult to control the high purity, particle size and solid solution uniformity of the synthesized powder in a good way. At the same time, it has the problems of high heat treatment temperature (generally requiring heating to above 1800℃) and high equipment cost.

[0005] To address the aforementioned problems, it is necessary to develop a novel method for preparing high-entropy carbide ceramic materials. Summary of the Invention

[0006] This invention provides a method for preparing high-entropy carbide ceramic materials based on polymer self-assembly. This method has the advantages of low synthesis and pyrolysis temperatures, simple process, and high controllability. The high-entropy carbide ceramic materials obtained have high purity and excellent thermal and mechanical properties.

[0007] The specific technical solution adopted is as follows:

[0008] A method for preparing high-entropy carbide ceramic materials based on polymer self-assembly includes the following steps:

[0009] (1) An organic compound and at least four transition metal acetylacetonates are added to an organic solvent and mixed and stirred to obtain a mixed solution; the organic compound is a phenolic compound or a benzyl alcohol compound, and the molar ratio of the organic compound to each transition metal acetylacetonate is 1:0.001 to 0.1, more preferably 1:0.01 to 0.1;

[0010] (2) Add resin crosslinking agent and catalyst to the mixed solution to carry out condensation reaction and obtain high-entropy carbide ceramic precursor solution;

[0011] (3) After washing and drying the high-entropy carbide ceramic precursor solution, high-entropy carbide ceramic precursor powder is obtained. The high-entropy carbide ceramic precursor powder is further pyrolyzed at 1500-1800℃ for 1-3 hours to obtain the high-entropy carbide ceramic material.

[0012] This invention proposes a method for preparing high-entropy carbide ceramic materials based on polymer self-assembly. The method utilizes the coordination reaction of transition metal acetylacetonate salts with phenolic or benzene alcohol compounds to form a complex. The complex then undergoes a condensation reaction with a resin crosslinking agent to self-assemble into a highly polymerized high-entropy carbide ceramic precursor. This precursor possesses a high concentration and uniform metal source, eliminating the need for the high-temperature diffusion process of metal ions in solid-phase carbothermal reduction reactions, thus lowering the reaction activation energy. Therefore, high-entropy carbide ceramic materials can be synthesized at relatively low temperatures.

[0013] The phenolic compounds include at least one of phenol, hydroquinone, phloroglucinol, and 4-methoxyphenol; the benzyl alcohols include at least one of benzyl alcohol, methoxybenzyl alcohol, and p-hydroxybenzyl alcohol.

[0014] The transition metal acetylacetonate may be selected from the acetylacetonate of group IV, V or VI transition metals; the organic solvent includes at least one of alcohol solvents (methanol, ethanol, isopropanol, etc.), ethyl acetate, tetrahydrofuran, and toluene.

[0015] The resin crosslinking agent is formaldehyde and / or paraformaldehyde, and the catalyst is an acid catalyst or an alkaline catalyst; further, the acid catalyst includes, but is not limited to, oxalic acid, and the alkaline catalyst includes, but is not limited to, NaOH, Ba(OH)2, Na2CO3, etc.

[0016] Preferably, in step (2), the amount of resin crosslinking agent added is 100 mol% to 400 mol%, and the amount of catalyst added is 0.5 mol% to 5 mol%, based on the molar amount of phenolic compounds or benzyl alcohols added to the mixed solution.

[0017] Preferably, in step (2), the condensation reaction conditions are a temperature of 95–150°C and a time of 1–3 h.

[0018] Specifically, in step (3), the pyrolysis is carried out under an inert gas atmosphere, such as a nitrogen atmosphere or an argon atmosphere.

[0019] The present invention also provides a high-entropy carbide ceramic material, which is prepared by the method for preparing high-entropy carbide ceramic materials based on polymer self-assembly. The general formula of high-entropy carbide ceramics can be expressed as MC (M = Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, W).

[0020] The high-entropy carbide ceramic material has a residual phase C content of less than 1 wt%. After heat treatment at 400-500℃ for 30-60 minutes in air atmosphere, the purity of the high-entropy carbide ceramic material can reach more than 99.9%.

[0021] This invention also provides the application of the aforementioned high-entropy carbide ceramic material in the field of high-temperature structural functional ceramics.

[0022] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0023] Compared with the traditional solid-phase powder high-energy ball milling method, the preparation method of the high-entropy carbide ceramic material of this invention does not require mechanical alloying and high-energy ball milling of raw materials. The pyrolysis process does not require special sintering equipment, and there is no oxidation or introduction of impurity elements during ball milling. It also eliminates the need for secondary crushing and ball milling, making the process route simple and safe. Compared with the existing carbothermic reduction method, this invention utilizes the coordination reaction of transition metal acetylacetonate salts with phenolic compounds or benzene alcohols to form complexes, and then obtains a polymer solution with uniform dispersion at the elemental molecular level through condensation reaction. The synthesized single-phase high-entropy carbide ceramic material has high purity, uniform and controllable composition and particle size, and the required pyrolysis temperature is reduced from above 2000℃ to below 1800℃. Compared with the molten salt method, it eliminates the need for a complex and tedious impurity removal process for the synthesized powder. Attached Figure Description

[0024] Figure 1 The XRD pattern of the high-entropy carbide ceramic material prepared in Example 1 is shown.

[0025] Figure 2 The XRD pattern of the high-entropy carbide ceramic material prepared in Example 2 is shown.

[0026] Figure 3 The XRD pattern of the high-entropy carbide ceramic material prepared in Example 3 is shown.

[0027] Figure 4 The XRD pattern of the high-entropy multiphase carbide ceramic material prepared in Comparative Example 1 is shown. Detailed Implementation

[0028] The present invention will be further illustrated below with reference to the embodiments and accompanying drawings. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Operating methods not specifically specified in the following embodiments are generally performed under conventional conditions or as recommended by the manufacturer.

[0029] Example 1

[0030] (1) Add 3.21g of niobium ethoxide and 4.10g of tantalum ethoxide to 2.5g of acetylacetone solution, and mix and reflux at 40℃ for 1h to obtain a solution containing niobium acetylacetone and tantalum acetylacetone.

[0031] (2) The solution obtained in step (1) was added to 72g of tetrahydrofuran solution along with 28.20g of p-methoxybenzyl alcohol, 37.62g of p-hydroxybenzyl alcohol, 2.68g of titanium acetylacetonate, 2.71g of vanadium acetylacetonate, and 3.56g of chromium acetylacetonate. The mixture was stirred for 2 hours to obtain a mixed solution.

[0032] (3) Add 0.23g of anhydrous oxalic acid and 122.84g of formaldehyde aqueous solution (formaldehyde mass fraction is 37wt.%) to the above-prepared mixed solution, reflux at 80℃ for 1h, and then transfer to a hydrothermal reactor and keep at 110℃ for 2h to obtain a polymerized high-entropy carbide ceramic precursor solution.

[0033] (4) The obtained high-entropy carbide ceramic precursor solution was washed with deionized water and filtered, and dried in a vacuum drying oven at 100°C to obtain high-entropy carbide ceramic precursor powder.

[0034] (5) The obtained high-entropy carbide ceramic precursor powder was pyrolyzed under argon protection at 1550℃ and kept at that temperature for 2h to obtain high-entropy carbide ceramic material.

[0035] Example 2

[0036] (1) Add 1.61g of niobium ethoxide and 2.05g of tantalum ethoxide to 1.25g of acetylacetone solution, and mix and reflux at 40℃ for 1h to obtain a solution containing niobium acetylacetone and tantalum acetylacetone.

[0037] (2) The solution obtained in step (1) was added to 88.11 g of ethyl acetate along with 34.54 g of p-methoxybenzyl alcohol, 1.34 g of titanium acetylacetonate, 1.35 g of vanadium acetylacetonate, and 1.78 g of chromium acetylacetonate. The mixture was stirred for 2 h to obtain a mixed solution.

[0038] (3) Add 0.23g of anhydrous oxalic acid and 22.5g of paraformaldehyde (divided into 10 batches) to the above-prepared mixed solution, reflux at 85°C for 1 hour, and then transfer to a hydrothermal reactor and maintain the reaction at 110°C for 2 hours to obtain a polymerized high-entropy carbide ceramic precursor solution.

[0039] (4) The obtained high-entropy carbide ceramic precursor solution was washed with deionized water and filtered, and dried in a vacuum drying oven at 100°C to obtain high-entropy carbide ceramic precursor powder.

[0040] (5) The obtained high-entropy carbide ceramic precursor powder was pyrolyzed under argon protection at 1550℃ and kept at that temperature for 2h to obtain high-entropy carbide ceramic material.

[0041] Example 3

[0042] (1) Add 1.61g of niobium ethoxide and 2.05g of tantalum ethoxide to 1.25g of acetylacetone solution, and mix and reflux at 40℃ for 1h to obtain a solution containing niobium acetylacetone and tantalum acetylacetone.

[0043] (2) The solution obtained in step (1) was added to 88.11 g of ethyl acetate along with 31.04 g of p-methoxyphenol, 1.34 g of titanium acetylacetonate, 1.35 g of vanadium acetylacetonate and 1.78 g of chromium acetylacetonate. The mixture was stirred for 2 h to obtain a mixed solution.

[0044] (3) Add 0.5g sodium hydroxide and 22.5g paraformaldehyde (divided into 10 batches) to the above-prepared mixed solution, reflux at 85°C for 1 hour, and then transfer to a hydrothermal reactor and keep at 110°C for 2 hours to obtain a polymerized high-entropy carbide ceramic precursor solution.

[0045] (4) The obtained high-entropy carbide ceramic precursor solution was washed with deionized water and filtered, and dried in a vacuum drying oven at 100°C to obtain high-entropy carbide ceramic precursor powder.

[0046] (5) The obtained high-entropy carbide ceramic precursor powder was pyrolyzed under argon protection at 1550℃ and kept at that temperature for 2h to obtain high-entropy carbide ceramic material.

[0047] Comparative Example 1

[0048] (1) Add 1.61g of niobium ethoxide and 2.05g of tantalum ethoxide to 1.25g of acetylacetone solution, and mix and reflux at 40℃ for 1h to obtain a solution containing niobium acetylacetone and tantalum acetylacetone.

[0049] (2) The solution obtained in step (1) was added to 88.11 g of ethyl acetate along with 31.04 g of p-methoxyphenol, 1.34 g of titanium acetylacetonate, 1.35 g of vanadium acetylacetonate and 1.78 g of chromium acetylacetonate. The mixture was stirred for 2 h to obtain a mixed solution.

[0050] (2) Add 0.5g sodium hydroxide and 22.5g paraformaldehyde (divided into 10 batches) to the above-prepared mixed solution, reflux at 85°C for 1 hour, and then transfer to a hydrothermal reactor and keep at 90°C for 2 hours to obtain a high-entropy carbide ceramic precursor solution.

[0051] (3) The obtained high-entropy carbide ceramic precursor solution was washed with deionized water and filtered, and dried in a vacuum drying oven at 100°C to obtain high-entropy carbide ceramic precursor powder.

[0052] (4) The obtained high-entropy carbide ceramic precursor powder was pyrolyzed under argon protection at 1400℃ and kept at that temperature for 2h to obtain high-entropy multiphase carbide ceramic material.

[0053] Sample Analysis

[0054] The XRD patterns of the high-entropy carbide ceramic materials prepared in Examples 1-3 are shown below. Figure 1-3As shown, this fully demonstrates that single-phase high-entropy (Ti,V,Cr,Nb,Ta)C ceramics can be synthesized according to the method of the present invention, and the composition of the product material is stable. Comparative Example 1 ( Figure 4 The synthesized ceramic materials contain a large number of impurity phases, and the composition is difficult to control effectively.

[0055] The embodiments described above provide a detailed explanation of the technical solutions of the present invention. It should be understood that the above descriptions are merely specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, additions, or similar substitutions made within the scope of the principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing high-entropy carbide ceramic materials based on polymer self-assembly, characterized in that, Includes the following steps: (1) An organic compound and at least four transition metal acetylacetonates are added to an organic solvent and mixed and stirred to obtain a mixed solution; the organic compound is a phenolic compound or a benzyl alcohol compound, and the molar ratio of the organic compound to each transition metal acetylacetonate is 1:0.001 to 0.1; the phenolic compound is at least one of phenol, hydroquinone, phloroglucinol, and 4-methoxyphenol; the benzyl alcohol compound is at least one of benzyl alcohol, methoxybenzyl alcohol, and p-hydroxybenzyl alcohol; the transition metal acetylacetonates are selected from the acetylacetonates of group IV, V, or VI transition metals; (2) A resin crosslinking agent and a catalyst are added to the mixed solution and a condensation reaction is carried out at a temperature of 95-150 °C for 1-3 h to obtain a high-entropy carbide ceramic precursor solution; the resin crosslinking agent is formaldehyde and / or paraformaldehyde, and the catalyst is an acid catalyst or a base catalyst; the acid catalyst is selected from oxalic acid, and the base catalyst is selected from NaOH, Ba(OH)2 or Na2CO3; the amount of resin crosslinking agent added is 100 mol% to 400 mol%, and the amount of catalyst added is 0.5 mol% to 5 mol%, based on the molar amount of phenolic compounds or benzyl alcohols added in the mixed solution; (3) After washing and drying the high-entropy carbide ceramic precursor solution, high-entropy carbide ceramic precursor powder is obtained. The high-entropy carbide ceramic precursor powder is then pyrolyzed at 1500-1800 °C for 1-3 h to obtain the high-entropy carbide ceramic material.

2. The method for preparing high-entropy carbide ceramic materials based on polymer self-assembly according to claim 1, characterized in that, The organic solvent includes at least one of alcohol solvents, ethyl acetate, tetrahydrofuran, and toluene.

3. The method for preparing high-entropy carbide ceramic materials based on polymer self-assembly according to claim 1, characterized in that, In step (3), the pyrolysis is carried out under an inert gas atmosphere, which is either a nitrogen atmosphere or an argon atmosphere.

4. A high-entropy carbide ceramic material, characterized in that, It is prepared by the method for preparing high-entropy carbide ceramic materials based on polymer self-assembly as described in any one of claims 1-3.

5. The application of the high-entropy carbide ceramic material according to claim 4 in the field of high-temperature structural functional ceramics.

Citation Information

Patent Citations

  • High-entropy carbide ultrahigh temperature ceramic powder and preparation method thereof

    CN109180189A

  • Composite carbide ceramic powder material as well as preparation method and application thereof

    CN116514553A

  • High-entropy carbide ceramic precursor, high-entropy carbide ceramic and preparation method

    CN115772034A